PERANCANGAN SMART DOOR LOCK MENGGUNAKAN VOICE RECOGNITION BERBASIS RAPBERRY PI 3 - Diah Aryani; Dedy Iskandar; Fitri Indriyani (UNIVERSITAS RAHARJA, 2018)
The server door is the main access to enter the server room. Currently the door lock on the server room is still done manually using the physical key as a tool to open or lock the door. Physical keys are easily lost or left behind which results in the officer not being able to enter the server room. This resulted in the officer can not access the server. Based on these reasons, the server door is integrated with a computer system that can unlock the door using voice recognition to unlock the server door. Voice recognition is able to identify a person through his voice. Voice recognition is divided into 2 parts namely speech recognition and speeker recognition. Meanwhile, the authors use the speech recognition section to open thedoor server door lock. Where, speech recognition can identify what is spoken by someone. The design of this tool is made using Raspberry pi 3 as the processing center and ULN2803 as ic to increase the voltage so that it can move the solenoid that serves to move the doorlock. Then raspberry gives command to the servo motor to open the door. Only staff who have id and password are only able to open the door lock on the server room using voice recognition. While those who do not have id and password can not unlock the door in the server room. So with the design of smart door lock tool using voice recognition raspberry-based pi 3 provides a level of security and access more computerized.